AKTIVITAS MARKETING PUBLIC RELATIONS PT SINTA PRIMA FEEDMILL UNTUK MENCIPTAKAN LOYALITAS PELANGGAN - Yoesof, Viola Ayu Yanti; Tresnawati, Yuni (Reputasi : Jurnal Public Relations, 2024)
This research aims to find out, understand and analyze the PR marketing strategy of PT Sinta Prima Feedmill using pull, push and pass strategies. The concept used is PR marketing activities, and pull, push and pass strategies. This concept uses research found in previous studies. Constructive qualitative methods were used for this research. The data collection technique used was primary through interviews with one key informant and two informants. Secondary data through journals, reference books, documents and the internet. Data analysis was carried out through data collection techniques, data reduction, data presentation and drawing conclusions. The research results show that PT Sinta Prima Feedmill uses 6 PR marketing activities, namely publications, identity media, events, news, social activities and sponsorship. Apart from that, to support PR marketing activities, they implement pull, push and pass strategies. PR’s marketing strategy and activities aim to maintain customer loyalty, with the advantage of strategic location as an added value that makes customers continue to choose PT Sinta Prima Feedmill.